2012
DOI: 10.1088/1367-2630/14/6/063016
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and transverse structure functions in high-Reynolds-number turbulence

Abstract: Abstract. Using exact relations between velocity structure functions [1-3] and neglecting pressure contributions in a first approximation, we obtain a closed system and derive simple order-dependent rescaling relationships between longitudinal and transverse structure functions. By means of numerical data with turbulent Reynolds numbers ranging from λ = 320 to λ = 730, we establish a clear correspondence between their respective scaling ranges, while confirming that their scaling exponents do differ. This diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 22 publications
(48 reference statements)
2
40
0
Order By: Relevance
“…The present velocity field (1.8) is an example of random process that exhibits a higher level of intermittency for the transverse case than for the longitudinal case. This is indeed a surprising effect, also observed in real flows (see discussions in Chen et al (1997), Dhruva, Tsuji & Sreenivasan (1997), Grauer, Homann & Pinton (2012)). In our model, only an analytical study could give a clear answer to this observed discrepancy, in particular in the asymptotic limit → 0.…”
Section: Numerical Estimationssupporting
confidence: 61%
“…The present velocity field (1.8) is an example of random process that exhibits a higher level of intermittency for the transverse case than for the longitudinal case. This is indeed a surprising effect, also observed in real flows (see discussions in Chen et al (1997), Dhruva, Tsuji & Sreenivasan (1997), Grauer, Homann & Pinton (2012)). In our model, only an analytical study could give a clear answer to this observed discrepancy, in particular in the asymptotic limit → 0.…”
Section: Numerical Estimationssupporting
confidence: 61%
“…The scaling exponents for second-order structure functions of δu r and δv r are indeed the same, but higher-order quantities can scale differently in principle [4], so there is no a priori assurance of principle that universality holds. The majority of the empirical evidence available, both experimental and numerical, shows that longitudinal and transverse structure functions indeed scale differently at higher orders [5][6][7][8][9][10][11][12][13], though some studies suggest otherwise [14,15]. Predicated on the consensus that the longitudinal and transverse structure functions scale differently, it was argued in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Table I summarizes the parameters of the simulations (see Ref. [19] for more details). In each case, the flow is seeded with 10 7 Lagrangian tracers.…”
mentioning
confidence: 99%